2012
DOI: 10.1016/j.fgb.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A defect in iron uptake enhances the susceptibility of Cryptococcus neoformans to azole antifungal drugs

Abstract: The high-affinity reductive iron uptake system that includes a ferroxidase (Cfo1) and an iron permease (Cft1) is critical for the pathogenesis of Cryptococcus neoformans. In addition, a mutant lacking CFO1 or CFT1 not only has reduced iron uptake but also displays a markedly increased susceptibility to azole antifungal drugs. Altered antifungal susceptibility of the mutants was of particular interest because the iron uptake system has been proposed as an alternative target for antifungal treatment. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 48 publications
(69 reference statements)
8
64
0
Order By: Relevance
“…This phenotype reverted upon the addition of iron to the medium. A similar observation has been made for Cryptococcus neoformans, where disruption of the genes encoding the ferroxidase (CFO1) and an iron permease (CFT1) of the high-affinity reductive iron uptake system resulted in increased susceptibility to azole antifungals (52). In the present study, we found that when UPC2 is intact, fluconazole exposure results in the upregulation of four genes associated with high-affinity iron uptake (FTR1, FET3, FET34, and FRP1).…”
Section: G980esupporting
confidence: 87%
“…This phenotype reverted upon the addition of iron to the medium. A similar observation has been made for Cryptococcus neoformans, where disruption of the genes encoding the ferroxidase (CFO1) and an iron permease (CFT1) of the high-affinity reductive iron uptake system resulted in increased susceptibility to azole antifungals (52). In the present study, we found that when UPC2 is intact, fluconazole exposure results in the upregulation of four genes associated with high-affinity iron uptake (FTR1, FET3, FET34, and FRP1).…”
Section: G980esupporting
confidence: 87%
“…Our previous transcriptome data showed that the gene CNAG_02565 was significantly downregulated in the cfo1 mutant, which suggested a possible connection between the gene function and the iron homeostasis and metabolism in C. neoformans [12]. The protein sequence of CNAG_02565 is highly homologous to Lys4, an enzyme in the lysine biosynthesis pathway in S. cerevisiae , with 64% similarity and 52% identity [21].…”
Section: Resultsmentioning
confidence: 99%
“…The protein encoded by S. cerevisiae LYS4 contains amino acid residues associated with an iron-sulfur (Fe–S) cluster and shows evolutionary conservation with the aconitase family of proteins [3,11]. The S. cerevisiae ortholog of LYS4 in C. neoformans was initially found in our transcriptome analysis to identify differentially expressed genes in a mutant lacking CFO1 , the gene encoding a ferroxidase for high-affinity iron transport at the plasma membrane [12]. The expression of LYS4 was significantly down-regulated in the cfo1 mutant, suggesting that Lys4 function may be associated with iron metabolism in C. neoformans .…”
Section: Introductionmentioning
confidence: 99%
“…Cellular levels of P, Na, Fe, and Zn were determined by inductively coupled plasma-atomic emission spectroscopy (ICP-AES) as described elsewhere (41). Briefly, cells were grown in YPD at pH 7.0, washed twice with water, frozen, and lyophilized.…”
Section: Methodsmentioning
confidence: 99%